Religious Service Attendance Aids Coping by Providing a Sense of Continuity: A Test of the Stress-Support Matching Hypothesis Using Mental Health Outcome Measures - Rainville, Gerard A. (Journal for the scientific study of religion, 2018)
We propose that religious service attendance (RSA) serves as a coping resource by providing a sense of continuity. As a source of continuity, and per the stress-support matching hypothesis, RSA should consistently buffer the negative mental well-being impacts of stressors related to discontinuity-the disruption of regular routines and relationships. Most, but not all, of the relevant previous studies we reviewed found that RSA served as an effective buffer for the negative mental health impacts of discontinuity stressors (such as unemployment, terminated relationships, etc.). This variability in previous findings warranted a formal exploration of the relationship between RSA and specific stressors. To that end, we conducted a series of OLS regression path analyses on a sample of Americans age 40 and older (N = 2,579). RSA was found to consistently buffer the negative impact of discontinuity stressors on mental well-being but failed to do so for other stressors. Overall, our observations are (a) consistent with the stress-support matching hypothesis, (b) suggest that RSA is particularly effective for reducing the negative impacts of discontinuity stressors, and (c) found no instance in which RSA exacerbated (i.e., made more severe) the effects of life event stressors on mental well-being.